Digitalization at work, Job Tasks and Wages: Cross-Country evidence from PIAAC1 - Sara De La Rica; Lucas Gortazar (Global Labor Organization (GLO), 2017)
The aim of the paper is threefold. First, we compute differences on job tasks (Abstract, Routine and Manual) across a harmonized and hence comparable sample of Anglo-saxon, many European and even Asian advanced countries. We do so by using very precise information on job contents at the worker level, which allows for job task heterogeneity within occupations. Second we assess the extent to which computer adoption leads to the observed differences of job contents across countries. Third, we test the impact of tasks at work on average wages and wage inequality. Our results show remarkable differences in the degree of polarization of job contents across countries, being computer adoption at work a key significant driver of such differences. In particular, ICT use at work explains 10.0% (7.7%) of the cross-country conditional differences in Abstract (Routine) tasks at work. Finally, our results indicate that although differences in tasks explain an important and significant part of wage differentials (similar to what is found in Autor and Handel, 2013), we cannot find a clear pattern in the explanation of wage inequality gaps by looking at differences in task endowments and task returns.
Keywords: J24; J31; O33; 330; Digitalization; Job Tasks; RIF-Regressions; Wage Decomposition; PIACC